Website Management in Developing E-Government in Karangpawitan Sub- District - Ayi Siti Nuraidah; Zikri Fachrul Nurhadi (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The development of information and communication technology is increasingly advanced day by day giving new life for humans to interact in the digital world. Technological advances that have occurred have made the government system transition to Electronic Government or E-Government. E-Government is the utilization of technology to improve accessibility and delivery of government services to stakeholders including employees, communities, and business partners. Through Presidential Instruction Number 3 of 2003 concerning Electronic Government Development Strategy, building website as a source of information is the first step in developing E-Government and this is one of the strategies to support good governance in Indonesia, namely through improving public information services. In Indonesia, many sub-district governments have not implemented an E-Government system in administering their governance, including Karangpawitan sub-district, Garut Regency. This community service aims to increase knowledge among Karangpawitan sub-district officials regarding the application of the E-Government concept and provide input regarding website development as a strategy in developing E-Government. The method used includes 4 (four) stages including first, data collection, source of the data collected includes primary and secondary data. Second, the preparatory stage, namely preparing all needs during implementation such as materials, targets and tools. At the implementation stage, namely the implementation of socialization activities. Finally, there is the evaluation stage, which is to see the feedback provided. The results of the community service received a good response from the Karangpawitan sub-district officials. The sub-district side welcomed the input submitted, as well as a decision from the Karangpawitan sub-district agency that it would immediately realize the creation of an official website to support better governance in the future